Feasibility of transdermal transport of atenolol by combination of iontophoresis and oleic acid pretreatment - Akhmad Kharis Nugroho; Arief Rahman Hakim; Marlyn Dian Laksitorini; Fajar Rakhmatullah; Eny Masruriati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Atenolol has a low oral bioavailability and a short elimination half-life. Therefore, alternative route and delivery system is important. Transdermal iontophoresis, i.e. a systemic drug delivery via the skin, implementing a low intensity of electrical current, is one attractive candidate. This study evalu ated feasibility of atenolol transdermal transport when iontophoresis is applied after enhancer pretreatment. There were 4 formulas prepared; 2 implemented iontophoresis for 3 hours (current density: 0.25 mA/cm2) while the others did not use iontophoresis. The enhancer was oleic acid (5 or 10% as a mixture in propylene glycol) with duration of pretreatment of one hour. Transport was evaluated in the diffusion studies across the fresh rat skin in a static-vertical diffusion system. Data were analyzed based on the numeric convolution method to obtain simulated Cp profiles as well as AUC of Cp profiles. Based on the simulated Cp, the best transport was achieved in Formula 3, where iontophoresis is performed across the skin, pretreated with 5% oleic acid for one hour. The value of simulated Cp indicated achievement of therapeutics level of atenolol, suggesting the feasibility of the atenolol delivery by iontophoresis.Key words : atenolol, transdermal, iontophoresis, enhancer